Theory Driven Evaluation Program MBG Berlandaskan Filosofi Halalan Ṭayyiban untuk Meningkatkan Kualitas Pendidikan di Indonesia - Moh Nasir; Zainul Arifin; Welly Kuswanto (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Abstract (maximum 250 words) This article offers a theory-driven evaluation of the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) in Indonesia by positioning the Qur'anic concept of halalan ṭayyiban as an evaluative philosophy rather than merely a normative slogan. The study responds to a gap in the literature: previous discussions of MBG have often described nutrition, charity, or food safety separately, while fewer studies have developed an explicit programme theory that connects Islamic ethical principles, food governance, and educational quality. Using a qualitative documentary design, this study analyses Tafsir Al-Mishbah on QS. Al-Baqarah 2:168, official policy documents, public programme reports, and relevant academic literature. Data were interpreted through framework analysis, pattern matching, and contribution analysis to construct a logic model covering inputs, activities, outputs, mechanisms, outcomes, and risks. The findings show that halalan ṭayyiban expands the evaluation criteria of MBG from calorie provision to a more comprehensive standard of legality, safety, hygiene, nutritional adequacy, dignity, equity, and educational benefit. The programme theory indicates that MBG can contribute to educational quality when nutritious and safe meals improve students' health, attendance, concentration, learning readiness, and trust in school-based public services. However, these outcomes depend on governance mechanisms, including supplier accountability, hygiene control, menu planning, certification, monitoring, and responsive feedback. The article contributes to theory-driven evaluation, Islamic educational ethics, and education policy by offering a value-based evaluative framework for improving MBG implementation in Indonesia.